IMPLEMENTASI DMAIC SIXSIGMA DALAM MENINGKATKAN LAYANAN PUSKESMAS X DI KOTA MALANG - Ayudya Mahendaringratry; I gede Asta Wido Herawan (Universitas Putera Batam, 2017)
Puskesmas (Pusat Kesehatan Masyarakat) are the direct service community of government health agencies to serve and should pay attention to the level of service to patients. The problems mostly is the lack of knowledge and skills of medical personnel and administrative personnel in dealing with patients and inform patient illness. To improve the service to the patient is the concept of DMAIC improvement with five stages. In this research, the worst cause of service is that the employees of Puskesmas X do not have the knowledge to answer the patient's question with the percentage of 62.8%. So the improvement is focused on the five causes of disabled services, which occurred in December 2016. Kata kunci: Kualitas Layanan, Lean Service, Six Sigma